The redox state of the alarmin HMGB1 is a pivotal factor in neuroinflammatory and microglial priming: a role for the NLRP3 inflammasome - Frank, Matthew G. (Brain Behav Immun, 2015)
The alarmin high mobility group box-1 (HMGB1) has been implicated as a key factor mediating neuroinflammatory processes. Recent findings suggest that the redox state of HMGB1 is a critical molecular feature of HMGB1 such that the reduced form (fr-HMGB1) is chemotactic, while the disulfide form (ds-HMGB1) is pro-inflammatory. The present study examined the neuroinflammatory effects of these molecular forms as well as the ability of these forms to prime the neuroinflammatory and microglial response to an immune challenge. To examine the neuroinflammatory effects of these molecular forms in vivo, animals were administered intra-cisterna magna (ICM) a single dose of fr-HMGB1 (10 µg), ds-HMGB1 (10 µg) or vehicle and basal pro-inflammatory effects were measured 2 and 24h post-injection in hippocampus. Results of this initial experiment demonstrated that ds-HMGB1 increased hippocampal pro-inflammatory mediators at 2h (NF-κBIα mRNA, NLRP3 mRNA and IL-1β protein) and 24h (NF-κBIα mRNA, TNFα mRNA, and NLRP3 protein) after injection. fr-HMGB1 had no effect on these mediators. These neuroinflammatory effects of ds-HMGB1 suggested that ds-HMGB1 may function to prime the neuroinflammatory response to a subsequent immune challenge. To assess the neuroinflammatory priming effects of these molecular forms, animals were administered ICM a single dose of fr-HMGB1 (10 µg), ds-HMGB1 (10 µg) or vehicle and 24h after injection, animals were challenged with LPS (10 µg/kg IP) or vehicle. Neuroinflammatory mediators and the sickness response (3, 8 and 24h after injection) were measured 2h after immune challenge. We found that ds-HMGB1 potentiated the neuroinflammatory (NF-κBIα mRNA, TNFα mRNA, IL-1β mRNA, IL-6 mRNA, NLRP3 mRNA and IL-1β protein) and sickness response (reduced social exploration) to LPS challenge. fr-HMGB1 failed to potentiate the neuroinflammatory response to LPS. To examine whether these molecular forms of HMGB1 directly induce neuroinflammatory effects in isolated microglia, whole brain microglia were isolated and treated with fr-HMGB1 (0, 1, 10, 100, or 1000 ng/ml) or ds-HMGB1 (0, 1, 10, 100, or 1000 ng/ml) for 4h and pro-inflammatory mediators measured. To assess the effects of these molecular forms on microglia priming, whole brain microglia were pre-exposed to these forms of HMGB1 (0, 1, 10, 100, or 1000 ng/ml) and subsequently challenged with LPS (10 ng/ml). We found that ds-HMGB1 increased expression of NF-κBIα mRNA and NLRP3 mRNA in isolated microglia, and potentiated the microglial pro-inflammatory response (TNFα mRNA, IL-1β mRNA and IL-1β protein) to LPS. fr-HMGB1 failed to potentiate the microglial pro-inflammatory response to LPS. Consistent with prior reports, the present findings demonstrate that the disulfide form of HMGB1 not only potentiates the neuroinflammatory response to a subsequent immune challenge in vivo, but also potentiates the sickness response to that challenge. Moreover, the present findings demonstrate for the first time that ds-HMGB1 directly potentiates the microglia pro-inflammatory response to an immune challenge, a finding that parallels the effects of ds-HMGB1 in vivo. In addition, ds-HMGB1 induced expression of NLRP3 and NF-κBIα in vivo and in vitro suggesting that the NLRP3 inflammasome may play role in the priming effects of ds-HMGB1. Taken together, the present results suggest that the redox state of HMGB1 is a critical determinant of the priming properties of HMGB1 such that the disulfide form of HMGB1 induces a primed immunophenotype in the CNS, which may result in an exacerbated neuroinflammatory response upon exposure to a subsequent pro-inflammatory stimulus.